The pathogenicity and reproduction capability of five epn strains on white grubs (Alissonotum impressicolle Arrow) in the laboratory conditions - Anh, Đỗ Tuấn; Tiền, Nguyễn Hữu; Châu, Nguyễn Ngọc (Vietnam Journal of Biotechnology, 2018)
Five entomopathogenic nematode strains, included 3 strains of the genus Steinernema, e.g. S-PQ16, SS-CP12 and S-TX1, and two strains of genus Heterorhabditis indica, e.g. H-CB3452 and H-KT3987 were evaluated on virulence and reproduction capacity on white grubs of black scarab (Alissonotum impressicolle Arrow) a serious pest damaging in the soils of sugarcane and many economic crops in Western Highland, particular Lam Dong province. The experiments were evaluated the pathogenicity virulence of EPN strains through establishing index as lethal concentration of 50 mortality percentage of host insects (LC50). While the reproduction capacity of EPN strains were established yield of infective juveniles (IJs) that produced inside insect cadavers. The bioassays on virulence of S-PQ16, S-CP12, S-TX1, H-CB3452 and H-KT3987 were revealed the mortality of white grubs as 93.3%, 86.7%; 93.3%; 86.7% and 73.3%, respectively, at the highest concentration of 5,000 IJs/insect. The 50% mortality of five indigenous strains was high levels with LC50 values ranged between 1,362 and 2,725 IJs. These values are also similar with our results previously on white grubs with some other EPN indigenous strains. It is also suitable with some evaluation bioassays of EPN on white grubs reported from China and Australia. The IJs yields from the insect cadavers were obtained up to 31×103 IJs with the strain S- CP12; 59.7×103 IJs with the S-PQ16 strain and 73.5×103 IJs with the strain S-TX1. Particularly, the highest yields were obtained from two strains of Heterorhabditis indica, viz. 125.1×103 IJs with H-KT3987 strain and 112.6×103 IJs with H-CB3452 strains. Respect to high virulence and also high reproduction capacity all these EPN strains should be satisfied the biological agents that can be used for biological control of white grubs of pests are living in the soil environment